2022
DOI: 10.1002/vzj2.20227
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing dual porosity in soil hydraulic properties using soil databases for pedotransfer function development

Abstract: Current databases of soil hydraulic properties (SHPs) have typically been used to develop pedotransfer functions (PTFs) to estimate water retention [θ(h)] assuming a unimodal pore-size distribution. However, natural soils often show the presence of bimodal to multimodal pore-size distributions. Here, we used three widely spread databases for PTF development: UNsaturated SOil hydraulic DAtabase (UNSODA) 2.0, Vereecken, and European hydropedological data inventory (EU-HYDI), to analyze the presence of structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…The results are in line with Y. Zhang, Weihermüller, et al. (2022), who found that, by relying on an extended soil database, including UNSODA, Vereecken, and EU‐HYDI, the joint fitting of soil water retention and hydraulic conductivity data (with Ks ${K}_{s}$ fixed and Ks ${K}_{s}$ fitted cases) outperformed the fitting of only soil water retention in terms of estimating hydraulic conductivity data. For a comprehensive comparison of different models in characterizing all the observed hydraulic conductivity data, please see Section 3.3.…”
Section: Resultssupporting
confidence: 87%
“…The results are in line with Y. Zhang, Weihermüller, et al. (2022), who found that, by relying on an extended soil database, including UNSODA, Vereecken, and EU‐HYDI, the joint fitting of soil water retention and hydraulic conductivity data (with Ks ${K}_{s}$ fixed and Ks ${K}_{s}$ fitted cases) outperformed the fitting of only soil water retention in terms of estimating hydraulic conductivity data. For a comprehensive comparison of different models in characterizing all the observed hydraulic conductivity data, please see Section 3.3.…”
Section: Resultssupporting
confidence: 87%
“…Also, authors have excluded the conductivity data > -6 cm pressure head, and estimated the VGM parameters, but then used the matching point conductivity (𝐾 0 [LT -1 ]; (Weynants et al, 2009;Zhang and Schaap, 2017a;Zhang and Schaap, 2017b) to describe datasets of WRC and HCC. This also indicates the presence of bimodality, something which has been corroborated by a systematic analyses of some data bases by Zhang et al (2022). Although these models are often needed to adequately describe tabulated data of WRC and HCC (Zhang et al, 2022;Volk et al, 2016), there are currently no PTFs for multimodal VGM.…”
Section: Non-uniform Pore Size Density Distributionsmentioning
confidence: 73%
“…This also indicates the presence of bimodality, something which has been corroborated by a systematic analyses of some data bases by Zhang et al (2022). Although these models are often needed to adequately describe tabulated data of WRC and HCC (Zhang et al, 2022;Volk et al, 2016), there are currently no PTFs for multimodal VGM.…”
Section: Non-uniform Pore Size Density Distributionsmentioning
confidence: 73%
See 1 more Smart Citation
“…The presence of macropores is mainly related to soil structure rather than to the primary soil particles that identify the textural class of a soil (Shang and Li, 2019). The use of a bimodal or multimodal water retention function ensures a proper description of the pore-size distribution which is given by the aggregation of the primary particles into secondary and tertiary particles (Li et al, 2014;Haghverdi 2020;Hassan et al 2022;Zhang et al, 2022). The flexibility of PSD models based on a large number of parameters (Fredlund et al, 2000) enhance the prediction performance of the two physico-empirical PTFs analyzed in this study.…”
Section: Articlementioning
confidence: 99%